AB0975 The Heart in Rheumatic Fever: Frequency and Severity in Our Series. (9th June 2015) - Cuoco, F.; Di Landro, G.; Torreggiani, S.; D'Errico, M.M.; Petaccia, A.; Corona, F.
Abstract : Background: Rheumatic fever (RF) is an autoimmune phenomenon that occurs after infection with group A streptococcus. Inflammation of the joints, heart and brain results in the common clinical manifestation of arthritis, carditis and chorea. The major morbidity and mortality result from rheumatic heart disease (RHD). Objectives: To retrospectively evaluate the demographic features, clinical characteristics and outcome among RF/RHD cases admitted in our Hospital in the last 35 years. Methods: Clinical and instrumental data of 359 RF cases observed between 1980 and 2014 were retrospectively evaluated. The clinical features of RF were classified according to the revised Jones criteria. Of these patients (201 males and 158 females with mean age at onset of RF 8.4±2.6 years), 325 had acute RF (ARF), while 34 were an exception to the Jones criteria. Patients with acute RHD (ARHD) were divided into 2 groups: 218 aged >5 years and 21 aged <5 years, comparing the clinical characteristics and echocardiographic parameters. Valvular disease was studied by echocardiographic assessment with classification of severity in 3 degrees: mild, moderate and severe according to a qualitative and semi-quantitative assessment of the colour flow Doppler. We compared the follow-up for mitral regurgitation (MR) and aortic regurgitation (AR), either as isolated lesion or in combined mitral-aortic regurgitation (MAR), in order to assess their severity, the time course and the eventual resolution of valvular lesion. Results: The majority of patient is Caucasian born in Italy (93.9%). Commonest major clinical manifestation among RF patients was carditis (72.1%) followed by arthritis (57.9%), p<0.05. Commonest valvular lesion among RHD patients was MR (48.3%), followed by MAR (44.4%) and AR (6.2%). No patient aged <5 years presented AR. Higher severity of ARHD was observed in children aged <5 years (66.7% of moderate-severe carditis compared to 48.2% of children >5 years, p<0.05) and a slower healing (Graph I ). Conclusions: The study evidenced that carditis is the most common major clinical manifestation in our population. The prevalence of ARHD in preschool age is significant (8.8%) and higher than reported in the literature (2.5% - 5%). The valvulopathy was more severe in younger children, explaining the slower resolution time. References: WHO Expert Consultation on Rheumatic Fever and Rheumatic Heart Disease (2001: Geneva Switzerland). Rheumatic fever and rheumatic heart disease: report of a WHO Expert Consultation, Geneva, October 29–November 1, 2001. WHO Technical Report Series; 923. Geneva: World Health Organization; 2004. Tani LY et al. Rheumatic fever in children younger than 5 years: is the presentation different? Pediatrics 2003; 112: 1065-8. Canter B et al. Rheumatic fever in children under 5 years old. Pediatrics 2004; 114: 329-30. Disclosure of Interest: None declared